INDDEX24: An Innovative Global Dietary Assessment Platform to Scale Up the Availability, Access, and Use of Dietary Data. (29th May 2020) - Wafa, Sarah; Colaiezzi, Brooke; Some, Jerome; Bell, Winnie; Prata, Cathleen; Perlick, Hallie; Rogers, Beatrice; Coates, Jennifer
Abstract: Objectives: Regular collection and use of dietary data, particularly in low- and middle-income countries (LMICs), is hindered by the lack of available and accessible dietary data research infrastructure (e.g., accessible food composition tables (FCT), portion conversions, and standard recipes; electronic dietary assessment tools). INDDEX24 is a global dietary assessment platform that addresses these bottlenecks. Methods: Priority technical specification were drafted and reviewed by experts with extensive dietary assessment experience in LMICs. Specifications included use of the multiple pass 24-hour dietary recall method, offline data collection capability, contextual adaptability, and an interviewer-administered format. Existing dietary assessment platforms were evaluated against the technical specifications via a structured literature review and key informant interviews. An initial version of INDDEX24 was developed and tested through feasibility studies in Vietnam and Burkina Faso. Feedback from potential users of the platform was gathered during webinars. The platform was subsequently revised, and its relative validity, time, and cost compared to use of paper-based 24-hour dietary recalls were then evaluated in Vietnam and Burkina Faso. Results: INDDEX24 is comprised of a mobile application (app) that is linked with a web app. The web app is used by researchers to manage the dietary data inputs for their survey context (i.e., FCT data, recipes, food descriptors, and portion conversions). Users can search the web app for dietary data inputs and integrate them into their workspace or upload their own inputs. The INDDEX24 mobile app is a 24-hour dietary recall app that has been built using CommCare mobile platform technology. Users can adapt mobile app questionnaire text to their survey language and context, add survey modules, conduct data monitoring, and basic food matching. To maximize the time and cost saving benefits of the platform, a concerted effort will be needed to populate the web app with dietary data inputs from LMICs. Conclusions: The extensive consultative process and evidence driven design has produced a high-quality platform that balances flexibility of adaptation to a range of contexts with quality control and standardization. Funding Sources: Bill and Melinda Gates Foundation.